Role of Cone-Beam Computed Tomography in the Management of Periodontal Disease - V. Thomas Eshraghi; Kyle A. Malloy; Mehrnaz Tahmasbi (MDPI AG, 2019)
The goal of this paper was to review the current literature surrounding the use of cone beam computed tomography (CBCT) related to the diagnosis, prognostic determination, and treatment of periodontal diseases. A literature review was completed to identify peer-reviewed articles related to CBCT and periodontics. The results were filtered to pool only articles specific to CBCT and periodontal diagnosis, prognosis, and treatment/outcomes. The articles were reviewed and findings summarized. Author’s commentary on technological advances and additional potential uses of CBCT in the field of periodontics were included. There is evidence to suggest that CBCT imaging can be more accurate in diagnosing specific periodontal defects (intrabony and furcation defects), and therefore be helpful in the prognostic determination and treatment planning. However, at this time, CBCT cannot be recommended as the standard of care. It is up to the individual clinician to use one’s own judgment as to when the additional information provided by CBCT may be beneficial, while applying the As Low As Reasonably Achievable (ALARA) principle. With continued technological advances in CBCT imaging (higher resolution, reduced imaging artifacts, lower exposure, etc.) the author’s believe that CBCT usage will become more prominent in diagnosis and treatment of periodontal diseases.